Utilization of the YouTube Application in Learning Akidah Akhlak at Senior High School - Faris Fathurrohman; Mahrus As’ad; Widhiya Ninsiana; Bima Fandi Asy'arie; Al-Mahdi (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2024)
This research aims to (1) determine the current condition of Akidah Akhlak learning and (2) design Akidah Akhlak learning through YouTube media. Objek penelitian dilakukan di MAN 1 Lampung Timur. The method used in this research is Research and Development (R&D). This research uses the ADDIE model. There are five stages in the ADDIE development model. Several phases are carried out, namely (Analysis, Design, Development, Implementation, and Evaluation). The results of this research are: First, the process of learning moral beliefs is going well, such as teachers using lecture, discussion, demonstration and memorization methods. However, no innovation can be implemented in the teaching and learning process. Second, several applications such as Canva, Clipchamp, and Text Voice Free are supported in designing learning through the YouTube application. Then, quantitative data was obtained at the validation stage by six teams of validators consisting of material experts, who got 83.0%; learning design experts, who got a percentage of 83.0%; and learning media experts, who got a score of 83.0%. The category is Very Eligible. However, this research is only limited to the design stage so that future researchers can complete these five stages to obtain maximum data.